Duck plague virus US3 protein kinase phosphorylates UL47 and regulates the subcellular localization of UL47 - Deng, Liyao; Wan, Jieyu; Cheng, Anchun; Wang, Mingshu; Tian, Bin; Wu, Ying; Yang, Qiao; Ou, Xumin; Mao, Sai; Sun, Di; Zhang, Shaqiu; Zhu, Dekang; et al. (Frontiers in Microbiology, 2022)
Duck plague virus (DPV) belongs to the alphaherpesvirinae, causes high morbidity and mortality in waterfowl. UL47 is a large abundant structural protein in DPV, which means that UL47 protein plays an important role in virus replication. US3 protein, as a viral protein kinase in alphaherpesviruses, has been reported to be critical for DPV virion assembly. In this study, we over-expressed UL47 and US3 proteins and found that DPV UL47 protein was a phosphorylated substrate of US3 protein, which interacted and co-localized with US3 protein in the cytoplasm. US3-regulated phosphorylation of UL47 was important for the cytoplasmic localization of UL47 because non-phosphorylated UL47 was localized in the nucleus. The six sites of UL47 at Thr29, Ser30, Ser42, Thr47, Ser161, Thr775 were identified as the phosphorylation targets of US3 protein. In vivo, UL47 phosphorylation was also detected but not in US3-infected cells. US3 protein promoted the cytoplasmic localization of UL47 at the late stage of infection, and lack of US3 protein caused a delay of UL47 translocation to the cytoplasm. These results enhance our understanding of the functions of US3 during DPV infection and provide some references for DPV assembly.